2023
DOI: 10.3390/su152115369
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strength of High-Performance Soil-Cement: A New, Alternative, Sustainable Construction Material

Bernat Vinolas,
Maria del Mar Casanovas-Rubio,
Alexandre Christofaro Silva
et al.

Abstract: Soil-cement is a building material that is considered low-cost and has a low environmental impact. Despite its benefits, performance optimisation studies are scarce compared to other materials such as concrete. The possibility of obtaining soil-cement with improved characteristics, such as flexural strength, would enable the increased use of this product in new applications in construction. The aim of this study is to produce high-performance soil-cement (HPSC) specimens and to evaluate and compare this new ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…Anggraini et al [50] revealed that the coconut fibers could significantly enhance the flexural strength of cement-treated marine soil in the Selangor State of Malaysia. Moreover, Vinolas et al [51] found the method to enhance the flexural strength of cementtreated soil by adding 10.5% clay, 42.5% fine sand, and 48.5% coarse sand. The material dosage includes 23.5% cement and 76.5% of soil.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…Anggraini et al [50] revealed that the coconut fibers could significantly enhance the flexural strength of cement-treated marine soil in the Selangor State of Malaysia. Moreover, Vinolas et al [51] found the method to enhance the flexural strength of cementtreated soil by adding 10.5% clay, 42.5% fine sand, and 48.5% coarse sand. The material dosage includes 23.5% cement and 76.5% of soil.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…The probe was placed in the middle of the main face (Figure 1e). Thermal conductivity was calculated via Equation (2).…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…The construction sector is a major contributor to global economic growth, with a predicted increase of 70% by 2025 [1]. However, it also has a significant environmental impact, being a major source of pollution, waste production, and energy consumption [1,2]. In the EU, it accounts for 40% of energy usage and 36% of CO 2 emissions [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation